THE IMPACT OF AI TOOLS ON ARTISTIC CREATIVITY: CHATGPT AND DALL·E IN CREATIVE PROCESS - Alif Sukma Muclisin; Ayu Puspita Muclisin; Wahyu Ruhul Qudus Muchlisin; Djuli Djatiprambudi; Setyo Yanuartuti (Politeknik Negeri Jakarta, 2025)
This study investigates the impact of generative AI tools, specifically ChatGPT and DALL·E, on creativity in visual artworks. As creativity becomes increasingly co-produced with artificial intelligence, questions arise about how AI influences the creative process. This research uses a comparative experimental design with two participant groups: one creating artworks with AI assistance, and another without AI involvement, both working under the same theme and timeframe. A custom creativity scale developed by the researcher was used to evaluate the artworks, focusing on eight indicators: Creative Personality and Curiosity, Knowledge and Skills Expansion, Connection, Boldness, Originality, Fluency, Flexibility, and Elaboration. The results reveal a noteworthy contrast: while AI-assisted artworks often appear more visually impressive, they scored lower on the creativity scale. The non-AI group exhibited stronger performance in originality, personal expression, and conceptual connection. Conversely, the AI-assisted group showed higher fluency and elaboration, attributed to the expansive nature of prompt-based generation, but tended to lack depth and authenticity. These findings suggest that generative AI enhances certain aesthetic aspects but may suppress other critical dimensions of creativity. Rather than replacing human creativity, AI functions as a collaborative tool that reshapes the creative landscape. This study calls for a balanced perspective—recognizing AI as a transformative partner in art-making, while remaining attentive to ethical and educational implications in fostering genuine human–AI co-creativity.